Qi Field Effect of Acupuncture Time-Acupoints-Space in the Treatment of Long Coronavirus Disease and Coronavirus Disease 2019 Vaccine Adverse Reactions - Zhu, Miansheng (Chinese medicine and natural products, 2023)
Corona Virus disease 2019 (COVID-19) has become a serious challenge. On the one hand, there is not a single explanation of its pathological mechanism, which directly affects the treatment efficacy. On the other hand, the complicated symptoms of long COVID and COVID-19 vaccine adverse reactions involve multiple systems and the number of affected patients is large, which have attracted great attention. Acupuncture time-acupoints-space (ATAS) is a new acupuncture technique developed on the basis of four methods of day-prescription of acupoints (Na Jia method), hour-prescription of acupoints (Na Zi Method), eightfold methods of the sacred tortoise (Ling Gui Eight Methods), and eight methods of swift puncturing of needles (Fei Teng Eight Methods) in midnight-noon and ebb-flow doctrine (Zi Wu Liu Zhu). The main idea of ATAS is to use the orderly combination of time acupoints and space acupoints to construct a field to regulate qi movement and treat diseases through the qi field effect. In France, although traditional Chinese medicine cannot be directly used to treat COVID-19, hundreds of patients with long COVID and COVID-19 vaccine adverse reactions have been treated using the four methods of ATAS. With reference to the microcirculatory lesions in the pathological mechanism of COVID-19 in Western medicine, hour prescription of acupoints (Na Zi Method) of ATAS showed specific efficacy for long COVID.
Keywords: Acupuncture Time-Acupoints-Space; ATAS; long COVID; vaccine adverse reaction; hour-prescription of acupoints (Na Zi Method) of ATAS; COVID-19; microcirculatory lesions; qi field effect